Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10725-009-9414-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine catabolism influences antioxidative defense mechanism in shoots and roots of five wheat genotypes under high temperature stress

Abstract: Effect of high temperature stress on polyamine catabolism and antioxidant enzyme activity in relation to glutathione, ascorbate and proline accumulation was studied in five wheat (Triticum aestivum L.) genotypes (differently susceptible to temperature stress). High temperature significantly increased the activities of superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPX), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), glutathione reductase (GR) and glutathione S-transferase (GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 47 publications
5
36
0
Order By: Relevance
“…Increased GPX activity under HS in different genotypes of wheat, however, has been reported by few researchers (Goyal and Asthir 2010;Gupta and others 2013) which is in conformity with our observations. Increased GPX activity in HD2329 cultivar was also significant (Fig.…”
Section: Variations In Guaiacol Peroxidase (Gpx) Activity At Differensupporting
confidence: 94%
See 1 more Smart Citation
“…Increased GPX activity under HS in different genotypes of wheat, however, has been reported by few researchers (Goyal and Asthir 2010;Gupta and others 2013) which is in conformity with our observations. Increased GPX activity in HD2329 cultivar was also significant (Fig.…”
Section: Variations In Guaiacol Peroxidase (Gpx) Activity At Differensupporting
confidence: 94%
“…The activity showed a significant increase during pollination, grain-filling, and seed-hardening stages in response to 22°C (T 0 ), 30°C (T 1 ), and 35°C (T 2 ) for 2 h. However, non-significant differences in the activity of GPX were observed between heat stress of 35 and 40°C for 2 h at all the stages of growth. An increase in the GPX activity has, however, been reported in different genotypes of T. aestivum under HS (Goyal and Asthir 2010). A decrease in the b Fig.…”
Section: Variations In Guaiacol Peroxidase (Gpx) Activity At Differenmentioning
confidence: 93%
“…It has been suggested that stress-tolerant plants increased exogenous PAs level to a greater extent than sensitive ones and those with a higher number of amino groups (Spm and Spd) are more effective in scavenging of reactive oxygen species (ROS), produced under stress conditions, than Put (Kubiś 2008). A decrease in titers of individual fractions or total PAs has also been demonstrated, which indicated complex polyamine biosynthesis in response to stress (Goyal and Asthir 2010). It was also proposed that conjugated forms of PAs may be involved in the defense mechanism as controllers of free PAs transport and as regulators of the PAs-titer in stress conditions (Liu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PAs stabilises biological membranes and cellular structures by directly binding to membrane phospholipids, direct scavenging of free radicals, osmotic adjustment, maintaining a cation-anion balance and binding to the antioxidant enzymes and elevating their activities (Roychoudhury et al 2011). Alteration in PA content and catabolism have been shown in plants under stressful condition (Goyal and Asthir 2010). Diamine oxidase (DAO) and polyamine oxidase (PAO) produces H 2 O 2 via catabolism of PAs that is considered as a causative element for apoptotic cell death in plants (Kuehn and Phillips 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of proline is a widespread plant response to environmental stresses in plants (Chakraborty and Tongden 2005). Proline as an osmolyte, a ROS scavenger and a molecular chaperone, accumulate in rice tissues where it helps in promoting water retention and alleviating the negative effect of drought stress (Mostajeran and Rahimi-Eichi 2009;Goyal and Asthir 2010;Szabados and Savoure 2010). Measurement of antioxidants and osmolyte in response to aerobic (less water availability) condition may provide valuable information on the various strategies of the plant intended to remove ROS.…”
Section: Introductionmentioning
confidence: 99%